Strategi Komunikasi Organisasi PT Iradat Dalam Menjaga Citra Perusahaan - Al Fadjri Wirayudha; Azwar Munanjar; Elpa Hermawan (Jurnal Public Relations (J-PR), 2025)
This study aims to analyze the organizational communication strategies implemented by PT Iradat to maintain and preserve its corporate image as a human resource consulting firm that has operated for more than four decades. The distinctiveness of this research lies in examining a company that, despite not having a dedicated Public Relations division, continues to sustain a positive reputation within the highly competitive consulting industry. Employing a descriptive qualitative approach, data were collected through in-depth interviews and documentation to obtain a comprehensive understanding of the communication patterns occurring within the organization. The findings indicate that PT Iradat adopts communication strategies centered on cross-departmental collaboration, strengthened internal communication, and the effective application of vertical communication between management and employees. These strategies are essential in ensuring information alignment, fostering harmonious internal relations, and creating message consistency that supports the company’s image. The results of this study not only provide empirical insights into organizational communication practices within service-oriented companies but also contribute to the development of communication theory, particularly regarding image management in organizations that operate without a formal Public Relations unit.